1992
DOI: 10.1111/j.1365-2044.1992.tb03150.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactoid reaction to propofol

Abstract: Summary A case of an anaphylactoid reaction following the induction of anaesthesia is reported. Subsequent intradermal testing suggested propofol to be the causative agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…Typically, propofol is cited in literature to possess bronchodilating properties thereby decreasing wheezing and reducing exacerbations of asthma in the asthmatic individual [1,3]. However, bronchospastic episodes and other reactions following propofol administration have been documented [1,[4][5][6][7][8][9][10][11][12][13][14]. Previously proposed etiologies for propofol reactions include a phenomenon related to histamine release as well as a reactionary cascade secondary to various chemical compounds found in propofol [5][6][7].…”
Section: Discussionmentioning
confidence: 98%
“…Typically, propofol is cited in literature to possess bronchodilating properties thereby decreasing wheezing and reducing exacerbations of asthma in the asthmatic individual [1,3]. However, bronchospastic episodes and other reactions following propofol administration have been documented [1,[4][5][6][7][8][9][10][11][12][13][14]. Previously proposed etiologies for propofol reactions include a phenomenon related to histamine release as well as a reactionary cascade secondary to various chemical compounds found in propofol [5][6][7].…”
Section: Discussionmentioning
confidence: 98%
“…Propofol has also been recommended for the induction of anesthesia in patients with asthma in other reports [23,24]. Generally, propofol is thought to be a safer intravenous anesthetic agent in regard to histamine release reactions, however, some anaphylactoid reactions have been already reported [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical studies, propofol was suggested to have many advantages as an anesthetic induction agent because of its low incidence of allergic reaction [1][2][3][4], however, some anaphylactoid reactions have been reported with propofol including the development of weals on skin and bronchospasms [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Of the hypnotic agents used anaphylactic reactions are more often seen with thiopental and propofol, although as a group hypnotics are a rare cause [142][143][144]. Diagnosis is by skin and intradermal testing, although a RAST method for detecting IgE to thiopentone has been described [143].…”
Section: Hypnotics and Inhalant Agentsmentioning
confidence: 99%